Cervicogenic somatosensory tinnitus: An indication for manual therapy plus education? Part 2: A pilot study. (June 2016) - Oostendorp, Rob A.B.; Bakker, Iem; Elvers, Hans; Mikolajewska, Emilia; Michiels, Sarah; De Hertogh, Willem; Samwel, Han
Abstract: Objectives: The aim of this study was to evaluate the efficacy of Manual Therapy Utrecht (MTU) plus education in patients with cervicogenic somatosensory tinnitus (CeT). Study design: Pretest–posttest design. Method: Five hundred and six patients were referred or referred themselves. A subgroup of patients was identified with CeT, and within this a subgroup with tinnitus sensitization (TS). Two CeT groups were created based on the presence or absence of TS. Both groups underwent manual therapy combined with tinnitus education. Tinnitus intensity (VAS-tin 0–100 mm) was the primary outcome measure. Number of treatments and adverse effects were the secondary outcome measures. Results: A total of 122 patients with CeT (24.1%) were included (average age 53.3 years [±9.8], female 38.5% and duration of tinnitus 7.3 years [±8.9]). Patients were divided into two groups: 55 patients (45.1%) with TS (CeT + TS group) and 67 patients (54.9%) without TS (CeT − TS group). Pretest to posttest differences on the VAS-tin were statistically significant within both groups (CeT − TS group: difference VAS-tin 5.9 [ p = 0.01]; CeT + TS group: difference VAS-tin 18.2 [ p = 0.00]), and between the groups in favor of the CeT + TS group (difference VAS-tin 12.3 [ p = 0.01]). Pretest to posttest differences were clinically significant for the CeT + TS group (difference VAS-tin 18.2 [MCIC = ≥10 mm VAS-tin]) and between the groups (difference VAS-tin 12.3 in favor of the CeT + TS group). The average number of treatment sessions was 9.6 (±2.6) for the CeT − TS group and 10.3 (±2.5) for the CeT + TS group, a non-significant difference. There were no adverse effects in either group. Conclusions: Despite its limitations, this study provides valuable information on both the characteristics of patients with CeT and TS in a Dutch primary care manual therapy practice and on the potential effectiveness of MTU combined with tinnitus education for the subgroup of CeT + TS patients. Highlights: Evaluation of somatosensory tinnitus should be a regular feature in tinnitus patients. Manual therapists have a role in the management of patients with somatosensory tinnitus. Additional evidence is needed to verify the effectiveness of manual therapy. Verification of manual therapy with tinnitus education is needed.